Clinicopathological and molecular characterization of astroblastoma - Wu, Xiaoyan; Peng, Wenfeng; Zhang, Xu; Tang, Tao; Deng, Ling; Xu, Yuxia; Liu, Xiaoyun; Wang, Fang; Peng, Wujian; Huang, Jianrong; Zhong, Xiaoni (Frontiers in Molecular Neuroscience, 2025)
IntroductionAstroblastoma is a rare tumour of the central nervous system that often manifests with non-specific clinical symptoms and lacks distinct histological features. There is a pressing need for further understanding of the clinicopathological and molecular characteristics of Astroblastoma. Identifying mutant genes can aid in reliable and early diagnosis, as well as provide insights for the development of targeted therapies.MethodsThis study aims to investigate the clinicopathologic and molecular characteristics of astroblastoma. A total of four patients diagnosed with astroblastoma were included in the analysis. Clinical features, histological findings, and immunohistochemistry results were reviewed and analyzed. Genetic alterations were identified using fluorescence in situ hybridization (FISH) and next-generation sequencing (NGS), followed by patient follow-up.ResultsThe study included four female patients, ranging in age from 8 to 44 years. One patient had a tumour in the right parietal lobe, while the other three had tumours in the spinal cord. Histology is usually characterized by pseudorosettes of astroblasts and hyalinization of blood vessels. These tumors showed a growth pattern similar to traditional intracranial astroblastoma, and the histological manifestations of the four patients were all high-grade, showing features of high-density areas of tumor cells or necrosis. Immunohistochemical staining revealed that all four patients expressed OLIG2, EMA, and vimentin, while three patients also expressed GFAP and S-100. The Ki-67 positivity index was approximately 15% in three cases and 10% in one case. Fluorescence in situ hybridization (FISH) using break-apart probes showed EWRS1 breaks in three patients and MN1 breaks in one. Further DNA or RNA-targeted biallelic sequencing identified an EWSR1(Exon1-7)-BEND2(Exon2-14) fusion in case 1, and an EWSR1(Exon1-7)-BEND2(Intergenic) fusion in case 2. In case 3, an EWSR1(Exon1-7)-NUDT10(Intergenic) fusion was present, and in case 4, an MN1(Exon1)-BEND2(Exon2) fusion was identified. The EWSR1-NUDT10 gene fusion is a new fusion type in astroblastoma. The patients were followed up for 76.5, 17.6, 33.7, and 61.3 months, respectively. Three cases experienced tumour recurrences at the spinal cord site, with multiple recurrences in case 4.DiscussionOur study unveiled the distinctive clinicopathological and molecular mutational characteristics of astroblastoma, while also identifying rare mutated genes. Additionally, the detection of MN1 or EWSR1 gene fusion through FISH or next-generation sequencing can provide valuable insights into the molecular mechanisms and aid in the differential diagnosis of astroblastoma.